O livro dos meus dias: histórias de uma travessia cartográfica para corpo, desejo e divergência contadas em dança, poesia e imagem - Brito, Alessandra Araújo de (2023)
The Book of My Days is an autobiographical research that presents a cartographic route of self-production, accomplished by a neurodivergent person, in processes of seeing and moving oneself from experimentations with dance in image devices, involving photography, video and poetic writing. It approaches visual culture questioning the imperative conditioning of the images in the gaze regime, acting in the processing of subjectivation, in the construction of identities and social practices. In counterpoint, proposes active agencies of productions from other corporeities, founded on difference and singularity. Exploring relations between body, image and move, as an expression plan of a self writing, the research weaves lines of strength in becomings, dreams, shadows, memoirs and affections.